Analysis and Development of an Educational Game for Early Childhood Numeracy Learning through a Curriculum-Based and Functional Evaluation Approach - Misna Asqia; Nurfajriah Halimatuz Zahra; Siti Hujaimah; Rizky Putra Mulyadi; Amalia Rahmah (Teknika, 2025)
Digital transformation in education has become a crucial necessity in the era of globalization, especially in Early Childhood Education. Generation Alpha tends to comprehend information more easily through digital media, which requires educators to be creative in delivering learning materials using technology. Video games as educational media have been proven to enhance children's learning motivation and create a joyful learning atmosphere. However, uncontrolled use of digital devices raises concerns regarding excessive screen time. To address this challenge, this study aims to design and develop a curriculum-based educational numeracy game for Early Childhood Education that can be collectively played in class using a projector and directly supervised by teachers. The method employed is Research and Development using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research process includes curriculum analysis, numeracy content design, interactive game scenario development, and functional testing using black box testing. Test results show that all core features of the application function as designed, with 100% validation. The educational game consists of three levels featuring various numeracy activities, pattern and shape recognition, tailored for Kindergarten levels A and B. This study demonstrates that pedagogically designed educational games integrated with technology can serve as an engaging, interactive, and developmentally appropriate solution for early childhood numeracy learning.